Assessment of Physical Activity and Exercise Prescription in a Diverse Population using the Minnesota Questionnaire (RIAF. International Journal of Physical Activity, 2026)
Abstract Introduction: Physical activity plays a crucial role in promoting health and preventing chronic non-communicable diseases. In university settings, it is essential to maintain both physical and mental balance.Objective: To assess physical activity levels and propose an appropriate exercise prescription using the Minnesota Leisure-Time Physical Activity Questionnaire.Methods: A descriptive study was conducted with a sample of 26 individuals from diverse backgrounds, including university students, relatives, and friends. The Minnesota Questionnaire was applied to estimate energy expenditure and classify participants into four categories: very active, active, moderately active, and sedentary.Results: Most participants were classified as very active, followed by active and a small group of moderately active individuals. Collective activities such as football and handball predominated, showing a preference for group exercise.Conclusion: The findings provide a basis for developing personalized exercise recommendations that promote adherence to regular physical activity and support healthy lifestyles.
Keywords: Physical activity; Minnesota questionnaire; exercise; prescription; health